Influence of melatonin pretreatment and preconditioning by hypobaric hypoxia on the development of cortical photothrombotic ischemic lesion - Matějovská, I; Bernášková, K; Krýsl, D; Mares, J (Physiological research, 2008)
Photothrombotic model of ischemia (PT) is based on free radical-mediated endothelial dysfunction followed by thrombosis. Free radicals are also involved in hypoxic preconditioning. We tested the sensitivity of PT to preconditioning with hypobaric hypoxia and to pretreatment with melatonin. In adult Wistar rats, after intravenous application of Rose Bengal, a stereo-tactically defined spot on the denuded skull was irradiated by a laser for 9 min. The first experimental group underwent hypobaric hypoxia three days before irradiation. In the second experimental group, melatonin was applied intraperitoneally one hour before irradiation. Three days after irradiation, animals were sacrificed, the brains perfused, and stained with TTC. Ischemic lesions were divided into grades (I, II, III). In the control group (where no manipulation preceded photothrombosis), most animals displayed deep damage involving the striatum (grade III). The group pre-exposed to hypoxia showed similar results. Only 28.57 % of the melatonin pretreated animals exhibited grade III lesions, and in 57.14 % no signs of lesions were detected. Pre-exposure to hypoxia was not protective in our model. Pretreatment with melatonin lead to a significant reduction of the number of large ischemic lesions. This result is probably caused by protection of endothelial cells by melatonin.
Keywords: Rats; hypoxie; stupeň závažnosti nemoci; Free Radicals; neuroprotektivní látky; Hypoxia; Antioxidants; Light; Brain Ischemia; přivykání k ischémii; Neuroprotective Agents; Intracranial Thrombosis; světlo; mužské pohlaví; červeň bengálská; Rats, Wistar; krysa rodu Rattus; Ischemic Preconditioning; Rose Bengal; antioxidancia; mozková kůra; intrakraniální trombóza; zvířata; Melatonin; melatonin; endoteliální buňky; Cerebral Cortex; volné radikály; atmosférický tlak; Atmospheric Pressure; potkani Wistar; ischemie mozku; Severity of Illness Index; Male; Endothelial Cells; Animals